Hydraulic Characteristics, Residence Time Distribution, and Flow Field of Electrochemical Descaling Reactor Using CFD - Bolin Hu (MDPI AG, 2021)
This paper uses computational fluid dynamics (CFD) to simulate flow field distribution inside an electrochemical descaling reactor in three dimensions. First, the reactor flow field was obtained by steady-state simulation, and the grid independence was verified. Then, the steady state of the flow field was judged to ensure the accuracy of the simulation results. Transient simulations were performed on the basis of steady-state simulations, and residence time distribution (RTD) curves were obtained by a pulse-tracing method. The effects of plate height and plate spacing on reactor hydraulic characteristics (flow state and backmixing) were investigated using RTD curves, and the results showed that increasing the plate height and decreasing the plate spacing could make the flow more similar to the plug flow and reduce the degree of backmixing in the reactor. The flow field details provided by CFD were used to analyze the reactor flow field and were further verified to obtain the distribution patterns of dead and short circuit zones. Meanwhile, information regarding pressure drops was extracted for different working conditions (490, 560, and 630 mm for pole plate height and 172.6, 129.45, and 103.56 mm for pole plate spacing), and the results showed that increasing the pole plate height and decreasing the pole plate spacing led to an increased drop in pressure. In this case, a larger pressure drop means higher energy consumption. However, increasing the pole plate height had a smaller effect on energy consumption than decreasing the pole plate spacing.